The Risk of Infection Human Papilloma Virus Infection in Acceptors of Depot Medroxyprogesterone Acetate Contraceptions - Aras, Baharuddin; Tahir, Mardiah; Arifuddin, Sharvianty; Hartono, Eddy; Chalid, Maisuri T. (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: Cervical cancer is the second most prevalent cancer inwomen around the world and the most common cancer in womencausing death. This study aims to analyze the connection betweeninfection of human papilloma virus (HPV) 16/18 and cervicalchanges in the acceptors of Depot Medroxyprogesterone Acetate(DMPA) Contraceptions and nonacceptors of Depot MedroxyprogesteroneAcetate (DMPA) Contraceptions.Methods: The research was conducted at the Public ServiceInstitution of Dr. Wahidin Sudirohusodo hospital, and privatemidwife clinics for seven months from December 2015 to June 2016.The research design is cross-sectional with. The samples were fortyacceptors of Depot Medroxyprogesterone Acetate (DMPA) and fortynon-acceptors of Depot Medroxyprogesterone Acetate (DMPA)contraception. Prevalence of HPV 16/18 and cervical cytologychanges were examine using the polymerase chain reaction andliquid base cervical cytology.Results: The results showed there was no significant relationshipbetween long-term use of DMPA contraceptives with HPV 16 and 18.There was no significant relationship between long-term use ofDMPA contraceptives with cervical cytology changes. There was nosignificant relationship between HPV 16 and 18 infections with theoccurrence of cervical cytology changes in long-term use of DMPAcontraceptives.Conclusion: The long-term use of DMPA contraceptive does notincrease the risk of HPV 16 and 18 infections. Also does not causecervical cytology changes that lead to cervical malignancy.Keywords: cervical cytology changes, Depot MedroxyprogesteroneAcetate (DMPA) contraception, HPV 16/18 infection